2007
DOI: 10.1002/tea.20206
|View full text |Cite
|
Sign up to set email alerts
|

Free‐choice worksheets increase students' exposure to curriculum during museum visits

Abstract: The museum visit is an important part of elementary school science teaching. However, a divide exists between teachers, who require curricular accountability, and museums, who emphasize free‐choice exploration. Can a carefully constructed worksheet bridge this divide by providing free‐choice exploration of curricular topics during the museum visit? In the present study, a theoretical framework was constructed to inform the design of worksheets as free‐choice learning devices. This framework was used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 39 publications
1
64
0
2
Order By: Relevance
“…During a field trip, active participation in structured museum activities (hands-on activities, inquiry-based problem solving, discussion with peers, etc.) promotes student motivation (S. Hidi, Weiss, Berndorff, & Nolan, 1998;Paris, Yambor, & Packard, 1998) and learning (Cox-Petersen, Marsh, Kisiel, & Melber, 2003;Mortensen & Smart, 2007;Tofield, et al, 2003). Educational impact is increased by post-visit activities (D. Anderson, et al, 2000;Davidson, et al, 2010;Griffin, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…During a field trip, active participation in structured museum activities (hands-on activities, inquiry-based problem solving, discussion with peers, etc.) promotes student motivation (S. Hidi, Weiss, Berndorff, & Nolan, 1998;Paris, Yambor, & Packard, 1998) and learning (Cox-Petersen, Marsh, Kisiel, & Melber, 2003;Mortensen & Smart, 2007;Tofield, et al, 2003). Educational impact is increased by post-visit activities (D. Anderson, et al, 2000;Davidson, et al, 2010;Griffin, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The study found a worksheet designed to help 8-11-year-old students on school trips to a museum supported students developing links between the museum and school science content (Mortensen & Smart, 2007). Finally, in China, exploratory research at the Shanghai Science and Technology Museum suggests that the History, Philosophy and Sociology of Science approach they have developed to frame science in their science education programme helps students (across age groups) connect museum and school science (Song & Zhao, 2012).…”
Section: Empirical Research On Social Inclusion/exclusion In Isementioning
confidence: 99%
“…Further evidence about how students learn in ISLEs can be gleaned from a design-based research study carried out in the USA (Mortensen & Smart, 2007). The study found a worksheet designed to help 8-11-year-old students on school trips to a museum supported students developing links between the museum and school science content (Mortensen & Smart, 2007).…”
Section: Empirical Research On Social Inclusion/exclusion In Isementioning
confidence: 99%
“…Findings from the field trip literature tell us that choice is essential for engaging students' interest and motivation (Bamberger & Tal, 2007), and that students learn best when guided by a clear agenda and scaffolding that supports knowledge integration across contexts and over time (Falk, Moussouri, & Coulson, 1998;Steier & Pierroux, 2011). Paper-based worksheets are one 'mobile' means of orienting students to a disciplinary domain in a museum setting, and this widely used approach has been shown to produce modest learning effects (Mortensen & Smart, 2007). Worksheets are shown to be most effective when the tasks provide a moderate amount of structure, intermediate levels of support (Bamberger & Tal, 2007), and are combined with opportunities for students to freely explore an exhibition (DeWitt & Storksdieck, 2008).…”
Section: Workheets and Video Tasksmentioning
confidence: 98%